Understanding and conceptualizing eSports among behavioural addictions: A brief overview of the literature. - Benedetta Ramella-Zampa; Giuseppe Alessio Carbone; Angelo Panno; Matheus Santos; Claudio Imperatori; Henning Budde; Eric Murillo-Rodriguez; Tetsuya Yamamoto; Sergio Machado (Elsevier, 2022)
The aim of the current overview was to present the existing literature on the recent phenomenon of eSports. Using a multifaceted approach, we focused on its definitions, historical development, and classification, drawing attention to key disputes that exist between scholars. Furthermore, we investigated the debate on whether eSports should be considered a traditional sport or not, with a particular interest in two processes that have contributed to eSports' development as a culturally-significant addition to the world of sports, as both a game and an occupation: sportification and professionalization. Lastly, we analysed studies on spectatorship and consumption to understand why people watch and play eSports pointing out data about the recent relationship between practice and the possible development of eSport's addiction, gambling, and the related impact on individual health and wellbeing.